KAFA’AH PERSPEKTIF HUKUM ISLAM DAN HUKUM ADAT JAWA SEBAGAI PERTIMBANGAN KHIYAR DALAM PERNIKAHAN - Misbachul Fitri, Abdul Basit; Najma Salsabila Sukma; Fitrotin Jamilah (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
Kafa’ah in linguistic terms is al musawah and al-mumathalah wich means blanc and equel blance, while in trems it is equality between husband and wife in perfection. Kafa’ah having a mean to reduce of domestic conflic between husband and wife, an also keep a encouyage the creation of happines, shaykh Abu Abdillah Alalaussy in the book ibanat al ahkam provides  an understanding that kafa’ah is a matter of religion, because marriage is a religious order and is wort worship. With religion, a person is expected to be able to carry out the teachings of his religion well, meanwhile, other kafa’ah factor,namely ineage, wealt, employment, independence status are supporting measures. It was also emphasized that apart from religion, the concept of kafa’ah is also recognized in the traditional of several etnic grups in indonesia, such as the batak, minang, dayak, and javanes. This concep involves several factors, wich, in general are actually similar to the factor in the concept of kafa’ah mentioned above, such as religion, leneage, and social status, these are considered benchmarks in determaining kafa’ah, thetefore, on this occasion, we will discuss the basic concepts  underlying kafa’ah, with a different  perspective, namely from the religious and javanes customary view puoints.